The Potential of the Quick Detection of Selectins Using Raman Spectroscopy to Discriminate Lung Cancer Patients from Healthy Subjects. (3rd October 2018) - Wolny-Rokicka, Edyta; Tukiendorf, Andrzej; Wydmański, Jerzy; Zembroń-Łacny, Agnieszka
Abstract : This study aimed at determining the concentration of P-selectins in lung cancer patients in different stages and healthy subjects. Then, the ability of the methodology developed to discriminate the existence of lung cancer was also evaluated. Serum spectra were obtained using Raman spectroscopy (RS). Blood samples were taken from subjects divided into two groups: group 1—comparing data from 22 patients clinically diagnosed with cancer before versus after medical intervention; group 2—comparing data from 10 palliative patients versus 17 healthy volunteers. The RS analysis of the samples revealed the presence of five very similar peaks in both groups 1 and 2. This leads to the conclusion that a medical intervention in cancer cases gives results comparable to those obtained from healthy subjects. The study indicates that the use of Raman spectroscopy can produce a better classification of cancer patients. However, diagnostically the results have not been statistically significant, probably due to the limited number of samples gathered. A larger number of samples would be required for future verification.